Developing a video-animated learning media of the human skeletal system using Powtoon - M. Mellisa; Chairun Nissa; Delma Saputri (Universitas Muhammadiyah Malang, 2023)
One is that audio-visual media can help students think creatively and find their understanding in mastering the material being taught, namely animated videos. An Animated video is a video that contains a movement of objects that are designed to be attractive with a specific purpose. This study aims to produce appropriate animated video learning media on human movement system material for class XI SMA Pekanbaru students. This study uses the ADDIE development model which consists of the stages of analysis, planning, development, implementation, and evaluation, and this research only reaches the development stage. Determination of the sample using a random sampling technique, and the number of samples is 10 students from each school. The data obtained in the development of this animated video media was by validating the material, media, and teachers, as well as looking at student responses to the media which was developed using student response questionnaires. The data analysis technique used the scale method with a Likert modification. The results of the validation by experts were in the Very Valid category and received very good responses from students. Based on the results of the validation and student responses, it can be seen that the validity level is very valid and it can be stated that the animated video learning media developed is very valid for use in learning. In addition, this animated video learning media still needs to be continued to the implementation and evaluation stages.